2022
DOI: 10.5194/acp-22-10505-2022
|View full text |Cite
|
Sign up to set email alerts
|

Significant continental source of ice-nucleating particles at the tip of Chile's southernmost Patagonia region

Abstract: Abstract. The sources and abundance of ice-nucleating particles (INPs) that initiate cloud ice formation remain understudied, especially in the Southern Hemisphere. In this study, we present INP measurements taken close to Punta Arenas, Chile, at the southernmost tip of South America from May 2019 to March 2020, during the Dynamics, Aerosol, Cloud, And Precipitation Observations in the Pristine Environment of the Southern Ocean (DACAPO-PESO) campaign. The highest ice nucleation temperature was observed at −3 ∘… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 91 publications
1
11
0
Order By: Relevance
“…Dust particles were a minor INP source at −12°C, but increased in importance at colder temperatures, contributing 10 to 40% of the INPs active at −19°C. These results are consistent with previous literature showing that bio-INPs make up a greater fraction of continental boundary layer INPs at warmer temperatures than at colder temperatures ( 19 , 25 , 36 ).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Dust particles were a minor INP source at −12°C, but increased in importance at colder temperatures, contributing 10 to 40% of the INPs active at −19°C. These results are consistent with previous literature showing that bio-INPs make up a greater fraction of continental boundary layer INPs at warmer temperatures than at colder temperatures ( 19 , 25 , 36 ).…”
Section: Resultssupporting
confidence: 93%
“…S6), environmental factors driving variability in bioaerosol emissions and concentrations are likely not fully captured by current models. For example, models currently do not represent the previously noted increases in bio-INP concentrations that frequently follow rainfall ( 25 , 33 , 34 , 36 , 37 ). Likewise, our simulations did not predict the increase in bio-INPs following precipitation (fig.…”
Section: Discussionmentioning
confidence: 99%
“…The number of heat-labile INPs can be seen as a proxy for the number of biological INPs in a sample. In order to quantify the presence of heat-labile INPs in the samples, a similar analysis was conducted as in Gong et al (2022). The atmospheric INP number concentration of the heated samples (N heated INP,air ) and its corresponding unheated samples (i.e., the full spectrum, see Sect.…”
Section: Quantifying the Contribution Of Heat-labile Inpmentioning
confidence: 99%
“…Past studies have shown that supercooled liquid water (SLW; liquid water at subfreezing temperatures) is especially common in SO clouds, and more prevalent than at similar latitudes in the Northern Hemisphere (NH), likely due to the lack of ice nucleating particles, which tend to increase glaciation rates, over the SO (Gong et al., 2022; Kanitz et al., 2011; Radenz et al., 2021; Vergara‐Temprado et al., 2018). SLW is particularly common within low clouds, although the ice phase becomes more prevalent at higher latitudes (Haynes et al., 2011; Huang et al., 2012).…”
Section: Introductionmentioning
confidence: 99%